Expression of the JAK/STAT Signaling Pathway in Bullous Pemphigoid and Dermatitis Herpetiformis. (24th October 2017) - Juczynska, K.; Wozniacka, A.; Waszczykowska, E.; Danilewicz, M.; Wagrowska-Danilewicz, M.; Wieczfinska, J.; Pawliczak, R.; Zebrowska, A.
Abstract : A family of eleven proteins comprises the Janus kinases (JAK) and signal transducers and activators of transcription (STAT) signaling pathway, which enables transduction of signal from cytokine receptor to the nucleus and activation of transcription of target genes. Irregular functioning of the cascade may contribute to pathogenesis of autoimmune diseases; however, there are no reports concerning autoimmune bullous diseases yet to be published. The aim of this study was to evaluate the expression of proteins constituting the JAK/STAT signaling pathway in skin lesions and perilesional area in dermatitis herpetiformis (DH) and bullous pemphigoid (BP), as well as in the control group. Skin biopsies were collected from 21 DH patients, from 20 BP patients, and from 10 healthy volunteers. The localization and expression of selected STAT and JAK proteins were examined by immunohistochemistry and immunoblotting. We found significantly higher expression of JAK/STAT proteins in skin lesions in patients with BP and DH, in comparison to perilesional skin and the control group, which may be related to proinflammatory cytokine network and induction of inflammatory infiltrate in tissues. Our findings suggest that differences in the JAK and STAT expression may be related to distinct cytokines activating them and mediating neutrophilic and/or eosinophilic infiltrate.